Enhancing the experience through smell - Spence, C (Institute of Food Science and Technology, 2016)
Prof. Charles Spence, Head of the Crossmodal Research Laboratory at Oxford University’s Department of Experimental Psychology, explains how olfactory augmentation in food and beverage design can enhance our enjoyment of the taste of food.